2020
DOI: 10.21475/ajcs.20.14.07.p2235
|View full text |Cite
|
Sign up to set email alerts
|

The application of zinc fertilizer reduces Fusarium infection and development in wheat

Abstract: Fusarium pseudograminearum and Fusarium graminearum commonly cause crown rot (FCR) and head blight (FHB) in wheat, respectively. Disease infection and spread can be reduced by the deployment of resistant cultivars or through management practices that limit inoculum load. Plants deficient in micronutrients, including zinc, tend to be more susceptible to many diseases. On the other hands, and zinc deficiency in cereals is widespread in Australian soils. Zinc deficiency may have particular relevance to crown rot,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The development of the pathogen can also be favored by weather factors, such as a cool and rainy spring, heavy rainfall, or sowing too deeply in heavy soil [9]. Infection can be prevented; several studies have shown that soil fertilization has a positive effect on plant tolerance to pathogenic fungi, particularly the use of fertilizers containing zinc or potassium phosphite [10][11][12]. Stalk rot usually occurs when plant tissues are damaged by Ostrinia nubilalis.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the pathogen can also be favored by weather factors, such as a cool and rainy spring, heavy rainfall, or sowing too deeply in heavy soil [9]. Infection can be prevented; several studies have shown that soil fertilization has a positive effect on plant tolerance to pathogenic fungi, particularly the use of fertilizers containing zinc or potassium phosphite [10][11][12]. Stalk rot usually occurs when plant tissues are damaged by Ostrinia nubilalis.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the agricultural practices should focus on the nutritional and structural needs of both the plant and its microbiome. Several studies have shown that fertilization of the soil had positive effects on the plant tolerance to pathogenic fungi, such as using fertilizers containing either zinc or potassium phosphite [ 16 , 17 , 18 ]. The use of potassium phosphite in the growing media under greenhouse conditions resulted in lettuce protection against Fusarium oxysporum with a disease reduction varying from 11% to 46% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attention should therefore be focused on the nutritional and structural needs of both the plant and its microbiome. Several studies have shown that soil fertilization has had a positive effect on plant tolerance to pathogenic fungi, such as in instances where fertilizers containing either zinc or potassium phosphite have been used [14][15][16].…”
Section: Introductionmentioning
confidence: 99%